THE ONLY CERTAINTY IS UNCERTAINTY: REMOTE HEARING IN INDONESIAN ARBITRATION - Akbar, Amrul; Amalia, Prita (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2021)
The remote hearing practice emerges as an alternative to in-person hearing as the established practice in arbitration. Yet, the practice of remote hearing does not always agreed upon by the parties in certain circumstances. The lack of certain laws governing its application raises a number of issues surrounding its application in arbitration. This paper examines legal theories and principles in domestic procedure law, international arbitration law, and their implementation in practice through comparative cases, utilizing a normative legal and case analysis method. The study employs a descriptive-analytical approach to describe the relevant legal rules, as well as legal theories and their application in the study object. Secondary data was gathered from primary, secondary, and tertiary sources of law for the study. The study's findings indicate that the laws governing remote hearings in Indonesia are uncertain in terms of confidentiality, the need for consent, mandatory preparation, control, and, very crucially, enforcement of the arbitration award. In contrast, it should address the issues generated by its extensive role in arbitration. The Indonesian government can address the aforementioned issue by enacting a particular procedural legislation that contains provisions for remote hearings in arbitration practice.